2020
DOI: 10.1111/jav.02562
|View full text |Cite
|
Sign up to set email alerts
|

Winds at departure shape seasonal patterns of nocturnal bird migration over the North Sea

Abstract: On their migratory journeys, terrestrial birds can come across large inhospitable areas with limited opportunities to rest and refuel. Flight over these areas poses a risk especially when wind conditions en route are adverse, in which case inhospitable areas can act as an ecological barrier for terrestrial migrants. Thus, within the east-Atlantic flyway, the North Sea can function as an ecological barrier. The main aim of this study was to shed light on seasonal patterns of bird migration in the southern North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 65 publications
4
30
0
Order By: Relevance
“…We found that, in all flyways that we studied, facultative soaring birds were more selective for wind support than uplift when flying over the open sea. This confirms previous findings that birds aim at maximizing wind support, probably to reduce the time and energy required to complete their journeys [18,[21][22][23][24][44][45][46]. Our model also showed a positive effect of the interaction between wind support and ∆T.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that, in all flyways that we studied, facultative soaring birds were more selective for wind support than uplift when flying over the open sea. This confirms previous findings that birds aim at maximizing wind support, probably to reduce the time and energy required to complete their journeys [18,[21][22][23][24][44][45][46]. Our model also showed a positive effect of the interaction between wind support and ∆T.…”
Section: Discussionsupporting
confidence: 91%
“…This confirms previous findings that birds aim at maximizing wind support, probably to reduce the time and energy required to complete their journeys. [18,[21][22][23][24][44][45][46]. Our models also showed a positive effect of the interaction between wind support and ∆T.…”
Section: Discussionsupporting
confidence: 66%
“…The blue circle indicates the most probable departure area of the migrants on nights of high migration intensity in spring. The red circle indicates the most probable departure area of the migrants on nights of high migration intensity in autumn outside of the Netherlands according to Bradarić et al (2020).…”
Section: Radar Observations Of Migrationmentioning
confidence: 99%
“…Twice a year large flows of terrestrial birds migrate over the North Sea during the night (Lack, 1963a,b;Hüppop et al, 2006;Hüppop and Hüppop, 2011;Shamoun-Baranes and van Gasteren, 2011). The crossing mainly occurs between the lowlands of Netherlands and Germany and Norway (cca 540 km), Denmark and Netherlands (cca 300 km) and between United Kingdom and Netherlands (cca 200 km) (Lack, 1959;Shamoun-Baranes and van Gasteren, 2011;Bradarić et al, 2020). To cross such distances, a bird with the average airspeed of 16 m/s needs between 3.5 and 10 h in still air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation